Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 6 - Systems of Equations and Inequalities - 6-2 Solving Systems Using Substitution - Lesson Check: 2

Answer

(3,5)

Work Step by Step

We know that 3x-4=y. Thus, in the first equation, wherever we see y, we will substitute 3x-4, and then we will solve: $-2x +5(3x-4) = 19 \\\\ -2x + 15x -20 =19 \\\\ 13x = 39 \\\\ x=3$ We now plug x=3 back in: $ y=3(3)-4=5 $
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.